Listening to the Qur’an and its effect on the Soul between the past and the present (Islamic Sciences Journal, 2023)
Praise be to God whose righteous grace is completed, and peace be upon the final Prophet with whom God sealed the messages, and upon his family and companions and those who followed them in goodness until the Day of Miqat, and after:This research deals with listening to the Noble Qur’an, and listening to the Noble Qur’an has a profound effect on bringing the servant closer to his Lord - the Exalted and Most High -; Hearing the Noble Qur’an brings joy and happiness to the soul, and elevates it to the highest levels. The examples of the impact of the Noble Qur’an on souls are numerous, regardless of time and place, whether the souls are infidels or believers, and whether Arab souls know and taste Arabic the language of the Noble Qur’an, or they are almost non-Arab souls who know nothing about Arabic.